PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING PADA MATERI PELUANG UNTUK KELAS XII SMA/MA - Yogi Lesmana (Departemen Matematika, 2020)
This study aims to develop learning tools in the form of Student Worksheets (LKPD) on the opportunity material for class XII SMA / MA students by applying problem-based learning. This study also aims to produce a valid and practical problem-based learning based student worksheet. The development research uses the Plomp development model which consists of three stages, namely the initial stage (Preliminary Research), the development stage (Prototyping Phase), and the production phase. The initial assumptions consist of needs analysis, curriculum analysis, concept analysis and student analysis. The development phase is the stage for learning tools consisting of prototype 1, prototype 2, and prototype 3. In prototype 1, an independent evaluation is carried out. In prototype 2 an expert review was conducted by mathematics education experts to see the validity of the learning tools developed. In prototype 3, a One-to-One Evaluation was carried out by testing the validated LKPD on three students with heterogeneous cognitive abilities. The last stage is the measurement results to see the practicality of the LKPD through the results of a questionnaire conducted by students. Based on the results of the validity data analysis, it shows that the Student Worksheet based on problem based learning in terms of content, problem-based learning, language, presentation and graphics has a validity level of 81.17% with a very valid category. LKPD also met the practical criteria from the results of the questionnaires and interviews. Based on these results, it can be seen that the problem-based learning mathematics learning device on the opportunity material for class XII SMA / MA students can be declared valid and practical. Keywords—Student Worksheets(LKPD), Problem Based Learning Based, Opportunities